Problems of Survival of Small and Medium-Sized Enterprises - Lakis, Vaclovas (Ekonomika, 2004)
The place of small and medium-sized businesses in the economies of the EU, Lithuania and other countries is discussed, along with the specific features of their management, factors influencing their development and problems of financing their performance.